Diagnostic, prognostic and predictive relevance of molecular markers in gliomas - Brandner, Sebastian; Deimling, Andreas von (Neuropathology & applied neurobiology, 2015)
The advances of genome-wide ‘discovery platforms’ and the increasing affordability of the analysis of significant sample sizes have led to the identification of novel mutations in brain tumours that became diagnostically and prognostically relevant. The development of mutation-specific antibodies has facilitated the introduction of these convenient biomarkers into most neuropathology laboratories and has changed our approach to brain tumour diagnostics. However, tissue diagnosis will remain an essential first step for the correct stratification for subsequent molecular tests, and the combined interpretation of the molecular and tissue diagnosis ideally remains with the neuropathologist. This overview will help our understanding of the pathobiology of common intrinsic brain tumours in adults and help guiding which molecular tests can supplement and refine the tissue diagnosis of the most common adult intrinsic brain tumours. This article will discuss the relevance of 1p/19q codeletions, IDH1/2 mutations, BRAF V600E and BRAF fusion mutations, more recently discovered mutations in ATRX, H3F3A, TERT, CIC and FUBP1, for diagnosis, prognostication and predictive testing. In a tumour-specific topic, the role of mitogen-activated protein kinase pathway mutations in the pathogenesis of pilocytic astrocytomas will be covered.